2023
DOI: 10.3390/app13053335
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Utilization of 3D Blading in the Cantilevered Stator from Highly Loaded Compressors

Abstract: Three-dimensional blading is an efficient technique in compressor aerodynamic design, and its function mechanism in the cantilevered stator needs to be addressed. This paper focuses on the sweep and dihedral in the cantilevered stator and seeks to expose their effects through detailed flow field analysis. Results show that the forward sweep could alleviate the corner flow separation by preventing the accumulation of the secondary flow toward the corner region, resulting in stronger flow separation at the blade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This was initially investigated by Gao et al [1]. Flow field improvements in highly loaded compressors and aeroengines are studied numerically by Xu et al [2] and Lei et al [3], respectively. In both cases, it was observed that appropriate three-dimensional blading resulted in an increase in static pressure and a reduction in the influence of secondary flows.…”
Section: Book Contentsmentioning
confidence: 99%
“…This was initially investigated by Gao et al [1]. Flow field improvements in highly loaded compressors and aeroengines are studied numerically by Xu et al [2] and Lei et al [3], respectively. In both cases, it was observed that appropriate three-dimensional blading resulted in an increase in static pressure and a reduction in the influence of secondary flows.…”
Section: Book Contentsmentioning
confidence: 99%